The role of SLC7A11 in diabetic wound healing: novel insights and new therapeutic strategies - Zhang, Wei; Feng, Jiawei; Ni, Yiming; Li, Gen; Wang, Yuqing; Cao, Yemin; Zhou, Mingmei; Zhao, Cheng (Frontiers in Immunology, 2024)
Diabetic wounds are a severe complication of diabetes, characterized by persistent, non-healing ulcers due to disrupted wound-healing mechanisms in a hyperglycemic environment. Key factors in the pathogenesis of these chronic wounds include unresolved inflammation and antioxidant defense imbalances. The cystine/glutamate antiporter SLC7A11 (xCT) is crucial for cystine import, glutathione production, and antioxidant protection, positioning it as a vital regulator of diabetic wound healing.Recent studies underscore the role of SLC7A11 in modulating immune responses and oxidative stress in diabetic wounds. Moreover, SLC7A11 influences critical processes such as insulin secretion and the mTOR signaling pathway, both of which are implicated in delayed wound healing. This review explores the mechanisms regulating SLC7A11 and its impact on immune response, antioxidant defenses, insulin secretion, and mTOR pathways in diabetic wounds. Additionally, we highlight the current advancements in targeting SLC7A11 for treating related diseases and conceptualize its potential applications and value in diabetic wound treatment strategies, along with the challenges encountered in this context.